A rare case of rapid development of bullous lung - Rampradeep, Rishab; Gandadharan, V.; Gururaj, Prasanth (International Journal of Advances in Medicine, 2022)
Tuberculosis, although an ancient disease, affecting humans for millennia; continues to present in atypical ways. Whilst the development of bullous lung disease in patients suffering from Pulmonary Tuberculosis, has been reported, it remains an extremely rare phenomenon. The underlying mechanisms remain unknown, and potential causes have been hypothesized, including the role of Isoniazid as part of antitubercular therapy. We reported one such case of a rapid development of bullous lung as a complication of Pulmonary Tuberculosis.